Resilience in Bullying Victims: The Role of Emotion Regulation and School Climate with Self-Esteem as a Mediator - Virlia, Stefani; Pudjibudojo, Jatie K.; Rahaju, Soerjantini (Journal of Educational, Health and Community Psychology, 2024)
Bullying in schools has become a serious issue that affects the mental health of teenagers. Data shows that many victims of bullying in Indonesia experience various negative impacts, including low self esteem. Therefore, it is important to explore factors that support resilience, such as emotion regulation and school climate. Based on Bronfenbrenner's ecological theory, the interaction between individuals and their environment, particularly schools, can influence the development of resilience. This study aims to examine how emotional regulation and school climate contribute to resilience, with self-esteem as an important mediator. The research method used is quantitative with mediator analysis techniques. The respondents in this study numbered 642 individuals with characteristics aged 12-16 years and who had previously been victims of bullying. The sampling technique used is purposive sampling. The research scales used are the Child-Youth Resilience Measure (CYRM-R), Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA), Rosenberg Self-Esteem Scale, and School Climate Scale. The research results show that the cognitive reappraisal strategy does not have  a direct impact on resilience but has an effect through self-esteem. Other results indicate that the school climate directly affects resilience and also has an effect through self-esteem. The use of adaptive emotion regulation strategies can enhance self-esteem, which in turn increases resilience. A positive school climate can also enhance self-esteem and resilience in facing various challenges.1